The mediating effect of job involvement in the relationship between tennis Instructors' perceived organizational justice and turnover intentions: a multi-group analysis across generations - Kim, Sujin; Kim, Jongho (Frontiers in Sports and Active Living, 2024)
This study aimed to analyze the role of job involvement as a mediator in the relationship between tennis coaches' perceived organizational justice and their intention to leave, and further, to identify any generational differences in this model. Using previous theories, perceived organizational justice was categorized into procedural and distributive justice, and job involvement into job attachment and job commitment. The study incorporated data from 201 coaches working at commercial tennis facilities nationwide. Results indicated that job involvement partially mediated the relationship between perceived organizational justice and turnover intentions, with distributive justice having a stronger total effect. The multi-group analysis identified generational variances. Distributive justice influenced turnover intentions more among the MZ generation, while procedural justice had a greater impact in the older generation. These findings offer valuable insights for commercial tennis facilities aiming to reduce turnover and manage generational conflicts, thereby enhancing organizational operation.